2015
DOI: 10.1039/c4cc10381e
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence turn-on detection of glucose via the Ag nanoparticle mediated release of a perylene probe

Abstract: A novel fluorescence turn-on strategy for glucose sensing is demonstrated. The fluorescence of a perylene probe could be quenched by the silver nanoparticles (Ag NPs). The Ag NPs could be etched by H2O2 generated from the enzymatic oxidation of glucose. And efficient probe fluorescence recovery was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…As shown in Fig. 15,27 The selectivity of developed hybrid nanosystem toward glucose over some possible interfering species was tested, including relevant glucide, ions, proteins and amino acids. In contrast, upon the sole addition of glucose or GOx, no obvious UCL signal was observed, suggesting that the glucose or GOx itself had no influence on the DNA-AgNPs/UCNP nanosystem.…”
Section: Glucose Sensing In Aqueous Buffermentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 15,27 The selectivity of developed hybrid nanosystem toward glucose over some possible interfering species was tested, including relevant glucide, ions, proteins and amino acids. In contrast, upon the sole addition of glucose or GOx, no obvious UCL signal was observed, suggesting that the glucose or GOx itself had no influence on the DNA-AgNPs/UCNP nanosystem.…”
Section: Glucose Sensing In Aqueous Buffermentioning
confidence: 99%
“…21 It has been demonstrated that AgNPs can be grown on a variety of templates, including proteins, 22 and polymers. 27 However, it involves the sophisticated and laborious probe preparation. For example, Yu's group demonstrated an approach for fluorescent detection of glucose by utilizing AgNPs and perylene probe.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the perylene probe can induce aggregation of the gold nanoparticles because of the strong π-π stacking and hydrophobic interactions (Jiao et al, 2014;Wang et al, 2011b). Li et al (2015) observed that silver nanoparticles (Ag NPs) can interact strongly with Pery-1 through electrostatic attractive and hydrophobic interaction. The probe fluorescence is efficiently quenched.…”
Section: Nanoparticle Induced Aggregation Of the Perylene Derivativesmentioning
confidence: 99%
“…Quenching of probe monomer fluorescence Perylene derivatives Pery-1 Wang and Yu (2010), Wang et al (2010a), Yang et al (2012), Ju et al (2012), Yang et al (2011), Guo et al (2013), Li et al (2015), Wang et al, (2011a), Fu et al (2013) …”
Section: Probes Referencesmentioning
confidence: 99%
“…AgNPs can also be oxidized by traces of Hg(II), forming Ag(I) and Ag/Hg amalgam 28, 29 . In addition, AgNPs are excellent quenchers of various luminescence probes, such as organic dyes and quantum dots (QDs) 3032 .…”
Section: Introductionmentioning
confidence: 99%